A Responsible Europe?
XIV, 240 p.
Keywords: A Responsible Europe? seeks to understand the EU's global role from a distinct normative perspective. It identifies moral principles that could serve as guidelines for a responsible role of the EU in global affairs, and applies these principles to selected policy areas and regional co-operation frameworks.